2020
DOI: 10.3390/nu12082230
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Rural Adolescents’ Dietary Diversity and Its Socioeconomic Correlates: A Cross-Sectional Study from Matlab, Bangladesh

Abstract: The majority of 36 million Bangladeshi adolescents live in rural areas. Improved understanding of their dietary patterns is of great public health importance. This study aimed to explore dietary diversity (DD) with its socioeconomic and gender stratification in a rural adolescent cohort and to isolate factors associated with inadequate DD. Household survey provided data for constructing dietary diversity scores (DDS) and assessing relevant socio-demographic variables. Final analysis included 2463 adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
34
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 67 publications
12
34
5
Order By: Relevance
“…According to this study, branded ice cream and sugar-sweetened beverages (soft drinks, energy drinks) were highly consumed by adolescents. This finding was in line with a previous finding where the consumption of sugar-sweetened beverages was found to be 13% among adolescents (Islam et al, 2020). The present study demonstrated that the adult population consumed puri, nimki, moglai, jilapi, alur chop more than other age groups.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to this study, branded ice cream and sugar-sweetened beverages (soft drinks, energy drinks) were highly consumed by adolescents. This finding was in line with a previous finding where the consumption of sugar-sweetened beverages was found to be 13% among adolescents (Islam et al, 2020). The present study demonstrated that the adult population consumed puri, nimki, moglai, jilapi, alur chop more than other age groups.…”
Section: Discussionsupporting
confidence: 94%
“…Among the school-going children, savory snacks like chips, chanachur, chutney, fried pulse consumption were prominent than other age groups. In a study of the 24-hour recall method among rural adolescents in Bangladesh, consumption of ultraprocessed sweets, confectionaries, and packaged products was 52% and consumption of savory snacks was around 35% (Islam et al, 2020). According to this study, branded ice cream and sugar-sweetened beverages (soft drinks, energy drinks) were highly consumed by adolescents.…”
Section: Discussionmentioning
confidence: 66%
“…A similar result was observed among Iranian women in another study by Kiani et al [14]. Thus, it is evident that the involvement of women in any kind of household decision-making can improve the DD and thereby their nutritional status [4,15,26].…”
Section: Discussionsupporting
confidence: 72%
“…Dietary diversity (DD), an essential component of dietary quality, is one of the benchmarks of the World Health Organization (WHO, 2009) for assessing an individual's feeding habits [10]. DD is characterized as the simple count of foods and food groups eaten during the previous 24 h, which is a good indicator of the improved nutritional adequacy of the diet [4,11,12]. In broad surveys and other data collection activities, DD is primarily used as a surrogate measure of micronutrient density or dietary adequacy [1].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Gujarat, India found that the higher family income was positively associated with the higher diversity score [29]. A study conducted in Bangladesh also stated the positive role of Socio-economic status in the MDD among adolescents [30].…”
Section: Discussionmentioning
confidence: 97%